Immunological features of the course of chronic non-healing Wounds and their immunocorrection (Herald of the National Children's Medical Center, 2025)
Background. To study the immunological features of chronic non-healing wounds (CNHW), determine the role of immunological parameters in the development of systemic inflammation, and evaluate the effectiveness of traditional immunocorrection.Materials and methods. An analysis was conducted on 84 patients with CNHW. Clinical manifestations, levels of CD20+ and CD23+ lymphocytes, cytokines (IL-1, TNF-α, TGF-β), immunoglobulins (IgA, IgM, IgG), as well as indicators of humoral and cellular immunity were assessed. The studies were carried out on days 1, 7, 14, and 28 of treatment.Results. Patients with systemic inflammation showed a significant increase in CD20+ and CD23+ cells, indicating a heightened B-cell immune response. T-lymphocyte deficiency and dysregulation of the immune regulatory index were observed. Immunocorrective therapy did not fully restore immune status, contributing to the chronicity of the process.Conclusion. CNHW are characterized by significant immune system dysfunction. The lack of adequate immunocorrection may lead to chronic sepsis. New therapeutic approaches considering immunological disturbances are necessary.
Keywords: Chronic non-healing wounds; immune system; immunocorrection; CD20 cells; CD23 cells; chronic inflammation; immunodeficiency; chronic sepsis; cytokines; tissue regeneration